(untitled) (At-Tibyan, 2024)
The concept of sakinah, mawaddah, and rahmah in the al-Qur’an emphasizes the central role of the family as the primary foundation of personal and social life. This study is particularly relevant in the context of contemporary muslim families facing challenges such as rising divorce rates, weakened communication, and shifting values. The research aims to explore the Qur’anic formulation of the ideal Islamic family through the method of tafsir maudhu’i (thematic exegesis). Relevant verses of the al-Qur’an were collected and analyzed descriptively with reference to both classical and contemporary exegetical works. The findings reveal that a family based on sakinah, mawaddah, and rahmah rests on three main pillars: a legitimate marital bond as the legal and moral foundation, spiritual commitment that fosters responsibility, and mutual affection that creates tranquility. The establishment of an ideal family is a shared responsibility of husband and wife through mutual understanding, empathy, and exemplary parenting. Furthermore, the family functions as the first and foremost educational environment, instilling values, morals, and character, with parental example playing a decisive role. Thus, a family grounded in sakinah, mawaddah, and rahmah not only pursues domestic happiness but also serves as an ethical model for society in accordance with Islamic teachings.